Veterinary image-guided interventions - Weisse, Chick; Berent, Allyson (Ames, Iowa : Wiley-Blackwell, 2015)
Veterinary Image-Guided Interventions is the only book dedicated to interventions guided by imaging technology. Written and edited by leading experts in the field, interventional endoscopy, cardiology, oncology and radiology are covered in detail. Chapters include the history and background of the procedures, patient work-up, equipment lists, detailed procedural instructions, potential complications, patient follow-up protocols, and expected outcomes. Split into body systems, the technical aspects of each procedure are presented using highly illustrated step-by-step guides. Veterinary Image-Guided Interventions is a must-have handbook for internists, surgeons, cardiologists, radiologists, oncologists and criticalists, and for anyone interested in cutting-edge developments in veterinary medicine. Key features include: -A highly practical step-by-step guide to image-guided procedures -Relevant to a wide range of veterinary specialists.-Written and edited by respected pioneers in veterinary image-guided procedures -A companion website offers videos of many procedures to enhance the text.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Veterinary endoscopy; Veterinary diagnostic imaging; Veterinary medicine -- Diagnosis; Radiography, Interventional -- methods; Radiography, Interventional -- veterinary; Diagnostic Techniques, Surgical -- veterinary; Surgery, Computer-Assisted -- veterinary; Medical; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Veterinary diagnostic imaging; Veterinary endoscopy; Veterinary medicine -- Diagnosis; Electronic books; Electronic books